1991
DOI: 10.3109/00207459108985446
|View full text |Cite
|
Sign up to set email alerts
|

Molecular anatomy of the neuro-immune connection

Abstract: Light microscopic immunohistochemistry was employed to elucidate and compare the presence, distribution, and coexistence of various peptides, neuroendocrine markers and enzymes of the catecholamine pathway in nerves supplying lymphoid tissues in a variety of mammalian species. All lymphoid organs and tissues receive innervation by fibers containing dopamine-beta-hydroxylase and/or tyrosine hydroxylase, neural markers like protein gene product 9.5, synaptophysin and neurofilament and a varied spectrum of peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(132 citation statements)
references
References 44 publications
3
128
0
1
Order By: Relevance
“…However, a number of more recent studies have shown that immune system cells can also be regulated by neurotransmitters (6)(7)(8)(9)(10)(11). Consistent with this, both primary and secondary lymphoid organs are highly innervated by sympathetic ends that store dopamine (DA) (12,13).…”
Section: Endritic Cells (Dcs) Are the Most Efficient Type Of Apcsmentioning
confidence: 73%
“…However, a number of more recent studies have shown that immune system cells can also be regulated by neurotransmitters (6)(7)(8)(9)(10)(11). Consistent with this, both primary and secondary lymphoid organs are highly innervated by sympathetic ends that store dopamine (DA) (12,13).…”
Section: Endritic Cells (Dcs) Are the Most Efficient Type Of Apcsmentioning
confidence: 73%
“…The secondary lymphoid tissues are abundantly innervated by the sympathetic nerves that store a large amount of dopamine, and nerve fibers are particularly concentrated around vascular endothelial cells (7). The concentration of dopamine in the synapse is estimated to be 100 -300 M (24).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that CCR7 and CXCR4, via their respective chemokine ligands, play important roles in homing of naive T cells to the secondary lymphoid tissues (21,37,38). Furthermore, dopamine is present in the secondary lymphoid tissues at high levels (7,8). We therefore next examined a potential cooperation of chemokines and dopamine in induction of chemotaxis in human naive CD8 ϩ T cells.…”
Section: Synergistic Effects Of Dopamine and Homeostatic Chemokines Imentioning
confidence: 99%
See 1 more Smart Citation
“…Two independent clonal cell lines expressing the highest level of RC8 mRNA (data not shown) were tested for binding with the fol- The homology of the putative G-protein-coupled receptor NLR to both the cytokine and neuropeptide family of receptors raises the question of its biological importance in neuroimmune connections. Several neuropeptides, such as neuropeptide Y, calcitonin generelated peptide, galanin and opiods, besides their wide distribution throughout the central and peripheral nervous system, have been demonstrated to be localized in nerve endings innervating lymphoid organs [23]. Interestingly, neuropeptide Y-positive nerve terminals were found in close apposition with lymphoid compartments of the rat spleen [24].…”
Section: Resultsmentioning
confidence: 96%